2012
DOI: 10.3762/bjnano.3.95
|View full text |Cite
|
Sign up to set email alerts
|

Highly ordered ultralong magnetic nanowires wrapped in stacked graphene layers

Abstract: SummaryWe report on the synthesis and magnetic characterization of ultralong (1 cm) arrays of highly ordered coaxial nanowires with nickel cores and graphene stacking shells (also known as metal-filled carbon nanotubes). Carbon-containing nickel nanowires are first grown on a nanograted surface by magnetron sputtering. Then, a post-annealing treatment favors the metal-catalyzed crystallization of carbon into stacked graphene layers rolled around the nickel cores. The observed uniaxial magnetic anisotropy field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Simulation models were built on the basis of some experimental results. In previous research, El Mel et al 31 and Tosic et al 21 produced graphene layers by annealing Ni−C systems in experiments, and Peng et al 20 demonstrated that the flat surface favors the formation of large graphene; thus, the flake Ni−C model, which has a large and flat surface, was built and optimized. As shown in Figure 1, the initial models of Ni− C alloys were built by randomly replacing nickel atoms with carbon atoms.…”
Section: Methodsmentioning
confidence: 99%
“…Simulation models were built on the basis of some experimental results. In previous research, El Mel et al 31 and Tosic et al 21 produced graphene layers by annealing Ni−C systems in experiments, and Peng et al 20 demonstrated that the flat surface favors the formation of large graphene; thus, the flake Ni−C model, which has a large and flat surface, was built and optimized. As shown in Figure 1, the initial models of Ni− C alloys were built by randomly replacing nickel atoms with carbon atoms.…”
Section: Methodsmentioning
confidence: 99%
“…The base-level nanostructures of a larger dimension can be prepared by using a lithographic method, such as laser interference lithography. Among various nanolithography techniques, laser interference lithography is one of the most efficient optical lithography techniques to create uniform nanopattern arrays over a large substrate area (wafer-level) with good control of the pattern periodicity [23,24], allowing many new applications in nanofabrication with superior simplicity and convenience [25][26][27][28][29][30][31][32][33][34]. In this optical lithography, vertical standing wave effects due to reflection of the incident light from the substrate surface cause serious scalloping profiles along the sidewalls of the patterned photoresist structures [35].…”
Section: Fabrication Schemesmentioning
confidence: 99%
“…This may shed light on the complexity of the behavior of these unique and extremely interesting magnetic systems. Also, hybrid structures of ferromagnetic superlattices, combined with two-dimensional materials such as graphene and silicene have the potential to revolutionize spin-injection and detection devices for spintronics [ 27 30 ]. The ferromagnetic materials are ideal contacts for creating these spintronic devices on, for example, a single layer of graphene [ 29 ].…”
Section: Discussionmentioning
confidence: 99%